Hoarding Concept according to Hinduism, Judaism and Islam - Khan, Muhammad Anees; Irfan ullah (Journal of Islamic and Religious Studies, 2016)
Hoarding is considered (Ihtikar) very abhorring and objectionable. It is the practice of keeping something in store and not bringing the same to the market so that prices may rise owing to this artificial dearth of supply in the market. Each religion of the world has agriculture rules. In these, rules about Hoarding play an important role. In non Semitic religions Hinduism is the largest religion of the world. Similarly in Semitic religions Islam is the second and Judaism is considered in third stage. All these three religions and there followers have good relation with agriculture .But among this, Islamic rules considers one of the best rules in the world. Because Hinduism agriculture rules affected by cast system and the other side Judaism rules is affected by customs and traditions. But still there are some points on which Hinduism, Judaism and Islam are completely supporting each others. Hoarding rules is one of them. This paper is consisting on hoarding rules in Hinduism, Judaism and Islam.